Silicon Allows Halving Cadusafos Dose to Control Meloidogyne incognita and Increase Cotton Development - Santos, Leticia Bernabe [UNESP] (2021)
Purpose The objective was to analyze the suppressive effect of silicon, isolated and associated with cadusafos, on Meloidogyne incognita and the development of cotton. Methods Experiment was carried out with cotton plants delineated in completely randomized design in a 4 x 2 factorial, with four treatments: water; silicon (2.0 mmol L-1); cadusafos (0.08 mL per pot) and cadusafos (0.04 mL per pot) + silicon (2.0 mmol L-1); combined with nematode's absence and presence. Inoculation were carried out in the pot containing 5000 eggs and second stage juveniles. Si was applied via fertigation in all pots conform water retention capacity of the substrate, maintained at 70%. At 69 and 185 days after plant inoculation, root diameter, height and length were measured and the accumulation of Si in the aerial part was determined and the nematode population in the cotton roots was estimated. Results The supply of Si via fertigation was efficient increasing Si accumulation in cotton plant. Estimated nematodes population at 69 days after plant inoculation was higher in the absence of control treatment, with a greater effect of the nematicide and a lower population of M. incognita compared to the other treatments, in plants grown in the parasite presence. However, at 180 days after plant inoculation nematode population in nematicide treatment did not differ from halving dose of nematicide plus silicon treatment, as both treatments decreased nematode population. Conclusion Si supply was efficient as a suppressive agent on M. incognita, increasing plant development infected with nematodes, compared to the control treatment, allowing halving cadusafos dose without jeopardize nematode control.